2016
DOI: 10.1155/2016/4865439
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Myxoma Hypervascularized from the Right Coronary Artery: An Interesting Cath Lab Finding

Abstract: Primary cardiac tumors are rare and approximately half of them are atrial myxomas. They rarely remain asymptomatic, especially if large. The imaging of a myxoma by contrast dye during coronary angiography is an infrequent sign, which clarifies the vascular supply of the tumor. We report herein an interesting and rare case of a left atrial myxoma hypervascularized from the right coronary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Regardless of technique, it is important to achieve complete resection of the tumor with a margin of safety to minimize chance of recurrence (13). With complete resection of the tumor, the risk of recurrence is approximately 3% (14, 15). Regular and long-term follow-up with clinical examinations and serial echocardiography is highly recommended (16), though a consensus on total duration of follow-up time has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of technique, it is important to achieve complete resection of the tumor with a margin of safety to minimize chance of recurrence (13). With complete resection of the tumor, the risk of recurrence is approximately 3% (14, 15). Regular and long-term follow-up with clinical examinations and serial echocardiography is highly recommended (16), though a consensus on total duration of follow-up time has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…3 In case of occurring a steal phenomenon caused by blood shunting, many surgeons ligate these feeding vessels before exision of mass. Marco et al 10 demonstrated the case of left atrial myxoma which was removed successfully after ligation of feeding artery.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed a number of articles on the blood supply of left atrial and right atrial myxomas. The various sources of blood supply to various myxomas reported are described in box 1 6–26The source of blood supply of some reported myxomasLeft atrial myxoma—from the right coronary artery 6–8 24…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…The shape of the myxoma is also important. This can be made out by the shape of the tumour blush 5 8 9. Myxomas can be polypoid, round or oval.…”
Section: Outcome and Follow-upmentioning
confidence: 99%